Perancangan SPBU Mandiri dengan Sistem Pembayaran Elektronik untuk Masyarakat Penerima BBM Bersubsidi Berbasis Arduino Mega 2560 R3 - Habib Akhyari; Emil Naf'an; Nanda Tommy W (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Public Fuel Filling Stations (SPBU) are important facilities that provide various types of fuel such as gasoline, diesel, and Pertamax to meet the needs of motorized vehicles. The existence of SPBU greatly helps the public in obtaining fuel at a more economical price compared to purchasing retail. However, the transaction system at SPBU generally still uses conventional methods, such as cash payments or the use of debit/credit cards that have not been fully integrated with an efficient digital system. The use of RFID (Radio Frequency Identification) technology has been implemented as a non-cash transaction method at several SPBUs, but this system still has various weaknesses, such as limited device compatibility and delays in transaction processing. This prompted the author to develop the concept of an independent SPBU based on modern technology that is more efficient and secure. The proposed innovation includes the use of contactless smart cards and coin acceptors for the payment system, allowing users to make self-service transactions without operator involvement. In addition, the author also added several supporting components such as proximity sensors, which function to detect the presence of vehicles or people around the SPBU area. These sensors can help in saving electrical energy by activating the system only when needed. Another component is a vibration sensor, which plays a crucial role in detecting excessive vibrations that could potentially cause leaks. If excessive vibration is detected, the system automatically closes the solenoid on the pump to prevent the risk of fire or damage. By integrating this technology, the autonomous gas station system is expected to improve operational efficiency, user convenience, and safety during the automatic refueling process. This development is expected to be an innovative solution for modernizing the gas station system in Indonesia.